ANALISIS PENGARUH IKLAN DAN CELEBRITY ENDORSER TERHADAP CITRA MEREK DALAM MENINGKATKAN MINAT BELI SHAMPOO PENTENE PADA MASYARAKAT KOTA PEKANBARU - Andrio Husein; Zulkarnain '; Taufiqurrahman ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to analyze the influence of advertising and celebrity endorser of the brand image in increasing buying interest shampoo pentene in Pekanbaru community. The sample in this study were obtained using a non-probability sampling that respondents who meet the criteria of population where these samples do not have the same opportunities to choose from, with the sample criteria are respondents who use Pantene shampoo products and pernha see the ad. By using the formula according to Rao Purba, obtained a total sample of 96 people. Methods of data analysis using path analysis with SPSS 21. The results showed that the variables of advertising, celebrity endorser positive and significant impact on the image of Pantene shampoo brand in Pekanbaru. Then the ad variables celebrity endorser brand image positive and significant impact on buying interest Pantene shampoo in Pekanbaru. Based on the results of the analysis showed that the path celebrity endorser advertising variables affect the buying interest with the brand's image as a mediating variable in Pantene Shampoo advertising in Pekanbaru. It is expected that the company can continue to increase the rent, the company must continue to create new versions of the ads, giving rise to a new interest because of television viewers are getting bored with the same ad. Companies can add new endorser to reach other market segments without replacing graceful as a major endorser is already very credible.Keywords: Advertising, Celebrity Endorser, Brand And Interests Buy